2004
DOI: 10.1128/aem.70.8.4996-5004.2004
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Trichoderma harzianum Peptaibols on Mammalian Cells

Abstract: Trichoderma species isolated from water-damaged buildings were screened for toxicity by using boar sperm cells as indicator cells. The crude methanolic cell extract from Trichoderma harzianum strain ES39 inhibited the boar sperm cell motility at a low exposure concentration (50% effective concentration, 1 to 5 g [dry weight] ml of extended boar semen ؊1 ). The same exposure concentration depleted the boar sperm cells of NADH 2 . Inspection of the exposed boar sperm cells by transmission electron microscopy rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 28 publications
1
55
0
Order By: Relevance
“…This point, while intriguing, did not represent the objective of this work, and other experiments should be carried out to answer it. Peptaibols exhibit a wide spectrum of biological activities including antibacterial, antifungal and antiviral effects (Szekeres et al, 2005;Daniel & Filho, 2007), induction of systemic plant-defence responses (Viterbo et al, 2007), tissue damage in insect larvae, and cytolytic activity toward mammalian cells (Peltola et al, 2004;Leitgeb et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This point, while intriguing, did not represent the objective of this work, and other experiments should be carried out to answer it. Peptaibols exhibit a wide spectrum of biological activities including antibacterial, antifungal and antiviral effects (Szekeres et al, 2005;Daniel & Filho, 2007), induction of systemic plant-defence responses (Viterbo et al, 2007), tissue damage in insect larvae, and cytolytic activity toward mammalian cells (Peltola et al, 2004;Leitgeb et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The vacuolation was truncated in the absence of Ca 2+ , giving rise to the hypothesis that Ca 2+ plays a pivotal role in autophagy-like cell death in pathogenic fungi. Peltola et al (2004) demonstrated that the crude methanolic cell extract from a T. harzianum strain dissipates the mitochondrial membrane potential of human lung epithelial carcinoma cells (A549 cell line). Our result is consistent with this.…”
Section: Discussionmentioning
confidence: 99%
“…Most research on peptaibols has focused on their biosynthetic pathways, conformational properties and amino acid sequences (Benedetti et al, 1982;Wiest et al, 2002). It has also been reported that peptaibols promote the inhibition of mitochondrial ATPase, uncoupling of oxidative phosphorylation, immunosuppression, inhibition of platelet aggregation and induction of fungal morphogenesis (Shima et al, 1990;Matsuzaki et al, 1991;Csermely et al, 1994;Katayama et al, 2001;Peltola et al, 2004). However, the antimicrobial mechanisms of peptaibols are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a microheterogenous mixture of 20-residue peptaibols isolated from an endophytic biocontrol strain of Trichoderma citrinoviride has been demonstrated to have antifungal activities against several important forest tree pathogens, thus implicating their role in biocontrol (28). The 18-residue peptaibols from T. harzianum have been shown to exhibit mammalian cytotoxicity (29). Peptaibols are synthesized by large multidomain enzymes known as non-ribosomal peptide synthetases (NRPSs) that assemble compounds from a remarkable range of precursors (including nonproteinogenic amino acids and hydroxy or carboxyl acids), which can be N-methylated, acylated, reduced, or epimerized (30,31).…”
mentioning
confidence: 99%